Analisis pengaruh harga nanas, produktivitas lahan, dan jumlah tenaga kerja terhadap tingkat produksi nanas di Desa Tangkit Baru, Kecamatan Sungai Gelam, Kabupaten Muaro Jambi - Asther Cessa Amalliya; Zulgani; Dwi Hastuti (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the effect of pineapple prices, land productivity, and labor on the level of pineapple production in Tangkit Baru Village, Sungai Gelam District, Muaro Jambi Regency during the period 2025. The methods used are descriptive analysis and quantitative analysis with the Cobb-Douglas production function approach. The data used is primary data collected through questionnaires from 150 pineapple farmers as respondents using the census method. The findings show that partially, pineapple price, land productivity, and labor variables have a positive and significant effect on pineapple production levels. The return to scale analysis shows a condition of Increasing Returns to Scale (IRTS) with an RTS value of 0.8931, indicating that proportional addition of inputs results in smaller increases in output. The results also show that simultaneously the variables of pineapple price, land productivity, and labor have a significant effect on the level of pineapple production. The coefficient of determination (R²) value of 75,45% indicates that the three variables can explain the variation in pineapple production, while the remaining 24,55% is influenced by other factors outside the model.